Knowledge, attitude, and intention to accept COVID-19 vaccine among patients with chronic diseases in southern Ethiopia: Multi-center study - Adella, Getachew Asmare; Abebe, Kelemu; Atnafu, Natnael; Azeze, Gedion Asnake; Alene, Tamiru; Molla, Simegn; Ambaw, Gizachew; Amera, Tekalign; Yosef, Amanuel; Eshetu, Kirubel; Yeshambel, Adisu; Nigatu, Dabere; et al. (Frontiers in Public Health, 2022)
Abstract Background: Most of the COVID-19 fatal cases and severe illnesses like acute respiratory distress syndrome occur in older adults and other people who have underlying medical comorbidities. Understanding patients with chronic disease’ knowledge, attitudes, and intention to take the COVID-19 vaccine and related factors are necessary to control the mortality of COVID-19 infection. Therefore, this study aimed to assess knowledge, attitudes, and intention to take the COVID-19 vaccine among patients with chronic disease in Southern Ethiopia. Methods and materials: A facility-based cross-sectional study was conducted among 409 patients with chronic diseases having a follow-up at the hospitals of the Southern region of Ethiopia from November 14, 2021, to December 24, 2021. A structured, interviewer-administered questionnaire was used to collect data. Bivariate and multivariable logistic regression was conducted to show the association of variables with knowledge, attitude, and intention to take the COVID-19 vaccine. The associations of variables were declared with the use of a 95% CI and P-value < 0.05. Results: Overall, 79.2%, 70.9%, and 58.2% of participants had good knowledge, favorable attitude, and intent to take the COVID-19 vaccine, respectively. Age ≥ 49 years old (AOR = 1.643; 95% CI = 1.008-3.060) and college and above level of education (AOR= 3.002; 95% CI = 1.897-5.021) were found to be signiﬁcantly associated with knowledge about COVID-19 vaccine. College and above level of education (AOR = 1.510; 95% CI = 1.002-3.975) and good knowledge (AOR = 3.560; 95% CI = 1.481-6.120) were found to be signiﬁcantly associated with intention to take COVID-19 vaccine. Conclusion and recommendation: Intention to take the COVID-19 vaccine was low among patients with chronic diseases to achieve herd immunity. Therefore, a holistic and multi-sectoral partnership is necessary for a successful COVID-19 vaccination campaign. Further health education and communication are very crucial methods to improve vaccine acceptance and lastly to achieve herd immunity.